Perubahan Kepemilikan Manajerial dan Perubahan Nilai Perusahaan - Muhammad Madyan; Riska Gita Pratiska; Himmatul Kholidah (Forum Manajemen Indonesia (FMI), 2018)
Managerial ownership is an important element in reducing the agency conflict that occurs in a firm. The ownership can provide manager’s incentives to perform optimally in achieving the firm’s goal to improve firm value. Managers in each firm will adjust their ownership to respond firm value. That adjustment can create a changes in managerial ownership. This study aims to examine the relation between changes in managerial ownership to changes in firm value that used a non-financial firms from 2009-2011 as a sample. The results show that negative changes on managerial ownership have a negative and significant to changes in firm value, while positive changes on managerial ownership have a positive and not significant to changes in firm value. Keywords: Managerial ownership, changes in managerial ownership, and changes in firm value